Practicality of Pancasila Education Modules Based on Problem Based Learning (PBL) in Elementary Madrasahs - Lia Aziza Rahmah; Saidah Ahmad; Nisa Aulia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the practicality of the Pancasila Education module based on Problem Based Learning (PBL) developed for learning in Madrasah Ibtidaiyah. This study uses a research and development method with a descriptive qualitative approach. The development model used adapts the ADDIE stages, which include analysis, design, development, limited implementation, and evaluation. The research subjects involved fourth-grade teachers and fourth-grade students at Madrasah Ibtidaiyah. Data collection techniques were carried out through observation, interviews, teacher and student response questionnaires, and documentation. Data analysis was conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the PBL-based Pancasila Education module was easy for teachers to use, helped facilitate problem-based learning, and received positive responses from students. Thus, the developed module has a good level of practicality and is suitable for use as teaching material to support Pancasila Education learning in Madrasah Ibtidaiyah.